2008
DOI: 10.1042/bj20071512
|View full text |Cite
|
Sign up to set email alerts
|

Negative-feedback regulation of FGF signalling by DUSP6/MKP-3 is driven by ERK1/2 and mediated by Ets factor binding to a conserved site within the DUSP6/MKP-3 gene promoter

Abstract: DUSP6 (dual-specificity phosphatase 6), also known as MKP-3 [MAPK (mitogen-activated protein kinase) phosphatase-3] specifically inactivates ERK1/2 (extracellular-signal-regulated kinase 1/2) in vitro and in vivo. DUSP6/MKP-3 is inducible by FGF (fibroblast growth factor) signalling and acts as a negative regulator of ERK activity in key and discrete signalling centres that direct outgrowth and patterning in early vertebrate embryos. However, the molecular mechanism by which FGFs induce DUSP6/MKP-3 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
160
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(176 citation statements)
references
References 55 publications
14
160
2
Order By: Relevance
“…Regulation of MKP3(DUPS6) expression is most often placed downstream of ERK signaling (63,64) and is thought to constitute a negative feedback loop to downregulate mitogenic signaling. Consistent with this conclusion, Mkp3/Dusp6 is often induced following ERK activation (65) and requires regulation by the transcription factor Ets1 (64,65). Upon expression, MKP3 is catalytically activated via its physical association with ERK (62,66,67).…”
supporting
confidence: 59%
“…Regulation of MKP3(DUPS6) expression is most often placed downstream of ERK signaling (63,64) and is thought to constitute a negative feedback loop to downregulate mitogenic signaling. Consistent with this conclusion, Mkp3/Dusp6 is often induced following ERK activation (65) and requires regulation by the transcription factor Ets1 (64,65). Upon expression, MKP3 is catalytically activated via its physical association with ERK (62,66,67).…”
supporting
confidence: 59%
“…As the sequence of DUSP6 promoter has recently been reported (Ekerot et al, 2008;Morrison et al, 2008), we investigated if DUSP1 was able to modulate DUSP6 expression by stimulating the promoter activity. Co-transfection of a DUSP6 promoter reporter vector (Prom DUSP6) and CTAPDUSP1, a strong and transient DUSP1 expression vector in 293T and H460 cells, induced the activation of DUSP6 by threefold and 1.5-fold, respectively (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been reported that ERK activity modulates DUSP6 expression in response to fibroblast growth factor (Ekerot et al, 2008), in H460 cells expression of DUSP1 increases both DUSP6 promoter activation and expression, thus maybe other kinases, such as p38a and/or JNK, should control DUSP6 expression by repressing its promoter. DUSP6 can be upregulated in specific cancers exhibiting aberrant RTK and ras/raf signaling such as NSCLC (Sato et al, 2006).…”
Section: Dusp1 Participates In Tumor Progression In Nsclcmentioning
confidence: 92%
“…However, another cause of ERK activation can be inhibition of ERK phosphatases, such as DUSP6 (Kondoh and Nishida, 2007). Both mathematical models and experimental data showed that DUSP6 was the principal time regulator of ERK signalling (Ekerot et al, 2008). Thus, we speculated that the cisplatin-mediated, delayed and long-lasting activation of ERK was, at least in part, because of inhibition of the ERK-specific phosphatase, DUSP6.…”
Section: Discussionmentioning
confidence: 99%